Evaluation of analgesic activity and acute toxicity of ketoprofen-nicotinamide multicomponent solids - Yudi Wicaksono; Lusia Oktora Ruma Kumala Sari; Biru Putri Ayu Istiqomah; Shofiatul Izzah Al Amaliyah; Dwi Setyawan (Faculty of Pharmacy, Mahidol University, 2022)
The objective of this study was to evaluate the analgesic activity and acute toxicity of the ketoprofennicotinamide multicomponent solid. The preparation of multicomponent solids was carried out by the solvent evaporation method. The characterization of multicomponent solids was carried out by powder x-ray diffractometer (PXRD), differential scanning calorimeter (DSC), and fourier transform infrared spectrometer (FTIR). Solubility test was carried out by shaking method and evaluation of analgesic activity-toxicity was carried out in vivo in mice strain BALB/c. The results showed that the ketoprofen-nicotinamide multicomponent solid formed a new solid phase with different characteristics from the initial components. The ketoprofen-nicotinamide multicomponent solid showed a significantly (p<0.05) increased solubility, which was 1.3 times compared to the solubility of pure ketoprofen. In the evaluation of analgesic activity, the treatment group of multicomponent solid at a dose of 3.25 mg/kg body weight showed significantly increased pain inhibition (p<0.05) compared to the treatment group of pure ketoprofen. The toxicity evaluation in experimental animals showed that the multicomponent solids did not cause a significant (p>0.05) increase in SGOT and SGPT levels compared to the control group. Observations on the stomach histology of experimental animals showed that the ketoprofen-nicotinamide multicomponent solid gave a lighter infiltration of neutrophil inflammatory cells when compared to the pure ketoprofen group.